Natural convection of alumina-water nanofluid in an open cavity having multiple porous layers - Miroshnichenko, Igor V.; Sheremet, Mikhail A.; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal (Pergamon-Elsevier Science Ltd, 2018)
Control of heat transfer performance is a main challenge in different engineering applications. The present paper deals with numerical simulation of porous layers effect on natural convection in an open cavity with a hot vertical wall and cold alumina/water nanofluid penetrated into the cavity from open boundary. Mathematical description of the considered problem is based on Navier-Stokes equations with a single-phase nanofluid approach and the Brinkman-extended Darcy model for porous layers under the local thermal equilibrium approximation. The control parameters are the Rayleigh number (Ra = 10(4)-10(5)), distance between the left wall and the first vertical porous layer (delta = 0.1-0.4), porous layers thicknesses (gamma(1) = 0.1-0.3 and gamma(2) = 0.1-0.3) and nanoparticles volume fraction (phi = 0-0.04), It has been found the heat transfer enhancement with nanoparticles concentration for small distance between the hot wall and the first porous layer (delta = 0.1). In the case of gamma(1) <= 0.2 a growth of the distance between the left wall and the first porous layer (delta >= 0.2) leads to the heat transfer rate augmentation. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Open cavity; Natural convection; Porous layers; Nanofluid; Numerical results